High accuracy absorption coefficients for the Orbiting Carbon Observatory-2 (OCO-2) mission: Validation of updated carbon dioxide cross-sections using atmospheric spectra. (December 2017) - Oyafuso, Fabiano; Payne, Vivienne H.; Drouin, Brian J.; Devi, V. Malathy; Benner, D. Chris; Sung, Keeyoon; Yu, Shanshan; Gordon, Iouli E.; Kochanov, Roman; Tan, Yan; Crisp, David; Mlawer, Eli J.; et al.
Highlights: Recent updates to CO2 cross sections used by the OCO-2 mission are validated. Absorption model based on multispectrum analysis provides lowest residual rms. Further work needed to eliminate systematic residuals in atmospheric spectra. Abstract: The accuracy of atmospheric trace gas retrievals depends directly on the accuracy of the molecular absorption model used within the retrieval algorithm. For remote sensing of well-mixed gases, such as carbon dioxide (CO2 ), where the atmospheric variability is small compared to the background, the quality of the molecular absorption model is key. Recent updates to the 1.6 µm and 2.06 µm CO2 absorption model used within the Orbiting Carbon Observatory (OCO-2) algorithm are described and validated. A set of 164 atmospheric spectra from the Total Carbon Column Observing Network (TCCON) is used to compare three models, both previous and current versions of absorption coefficient tables (largely derived from recent multispectrum fitting analyses targeted specifically at these bands) as well as a recent model constructed to use the HITRAN 2012 compilation. Both spectral residuals and retrieved column-averaged CO2 mixing ratios (XCO2 ) are included in the comparison. Absorption coefficients based on the updated multispectrum fitting analyses provide residuals comparable to or smaller than either the previous version of the multispectrum fits or the HITRAN 2012-based model. For the 2.06 µm band the updated model finds noticeably lower residuals for low water content cases. It is found that apart from a scaling factor the prior and updated absorption models result in similar retrieved values of XCO2 for the 2.06 µm band and a slightly different airmass dependence for the 1.6 µm band.